Features of influence of different modes of training on the dynamics of power performance bodybuilders on stage-specialized basic training - O.S. Slavityak (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : study the effect of various features on the structure and orientation of exercise routines on the level of development of force capabilities bodybuilders on stage specialized basic training. Material : studies participated 60 athletes (age 18-19 years, the experience of training - 5 years). The study used a method of determining the index of the training load for the power sports. Level security features athletes determined by control testing. Control of the studied parameters was carried out for 4 months training at intervals of 1 month. Results : it was found that under conditions similar level of fitness athletes and structure your workout performance power load and the nature of their changes depend on the particular mode of training (in this study - from the application of the basic sequence variative and isolation exercises). Conclusions : the use of pilot training in integrated mode with alternating motor activity using the basic priority and isolation exercises for no more than 2 microcycles have the most significant positive impact on the increase in power performance parameters of athletes (on average by 26.5% p <0.05)